2015
DOI: 10.1007/s11571-015-9361-1
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Mozart music reduces cognitive impairment in pilocarpine-induced status epilepticus rats

Abstract: Patients with temporal lobe epilepsy (TLE) often display cognitive deficits. However, current epilepsy therapeutic interventions mainly aim at how to reduce the frequency and degree of epileptic seizures. Recovery of cognitive impairment is not attended enough, resulting in the lack of effective approaches in this respect. In the pilocarpine-induced temporal lobe epilepsy rat model, memory impairment has been classically reported. Here we evaluated spatial cognition changes at different epileptogenesis stages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 51 publications
1
22
0
9
Order By: Relevance
“…The antiseizure effects of the Mozart music in mice models of epilepsy confirmed previously published observations in rats (34). Given the clinical evidence supporting antiseizure effects of Mozart music in patients with epilepsy (28,33,(35)(36)(37)(38)(39)(40)(41)(42)83), and preclinical evidence that the Mozart music can upregulate expression of BDNF in the rat hippocampus and reduce cognitive impairment in status epilepticus model in rats (54,84,85), our findings warrant further investigation in other models of epilepsy and epileptogenesis. This work also supports research on the Mozart music in canine epilepsy (86).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The antiseizure effects of the Mozart music in mice models of epilepsy confirmed previously published observations in rats (34). Given the clinical evidence supporting antiseizure effects of Mozart music in patients with epilepsy (28,33,(35)(36)(37)(38)(39)(40)(41)(42)83), and preclinical evidence that the Mozart music can upregulate expression of BDNF in the rat hippocampus and reduce cognitive impairment in status epilepticus model in rats (54,84,85), our findings warrant further investigation in other models of epilepsy and epileptogenesis. This work also supports research on the Mozart music in canine epilepsy (86).…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies suggested that exposure to the Mozart music had antiseizure effects in rat model of absence seizures (34), and can reduce cognitive impairment in rat model of status epilepticus (54). We tested effects of the Mozart playlist on seizures in the corneal kindling model of epilepsy in CF-1 mice.…”
Section: Epilepsy Studiesmentioning
confidence: 99%
“…The use of music in patients involve areas of the brain involved in cognitive and emotional processing (Schafer, Sedlmeier, Stadtler, & Huron, ). Music could enhance the brain‐derived neurotrophic factor level of dorsal hippocampus CA3 and dentate gyrus, and help to promote the recovery of cognitive damage caused by seizure activities (Xing, Chen, et al, ; Xing, Qin, et al, ; Xing, Xia, et al, ). Furthermore, sex differences have been demonstrated in different cognitive reactivity patterns induced by special effects of music in visuospatial and navigational working memory (Grabowska, ; Palmiero, Nori, Rogolino, D'Amico, & Piccardi, ).…”
Section: Discussionmentioning
confidence: 99%
“…γ oscillations and ripples are widely believed to correlate with the formation of cognition (12). Frequent seizures can lead to severe cognitive deficits (4648). Spatial memory deficits in the pilocarpine model of TLE have already begun during the latent period (47, 48) and cognitive deficits persist when animals had chronic spontaneous seizures.…”
Section: Discussionmentioning
confidence: 99%